2010
DOI: 10.1177/1403494810384426
|View full text |Cite
|
Sign up to set email alerts
|

Dietary, social, and environmental determinants of obesity in Kenyan women

Abstract: This study suggests that urbanisation and its associated economic advancement as well as changes in dietary habits are among the most important determinants of overweight and obesity in Kenyan women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
82
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(100 citation statements)
references
References 13 publications
16
82
2
Order By: Relevance
“…The higher proportion of overweight member women reflects this transition and is an area of concern. Energy from saturated fat remained below the recommended level (10 %) and median intake was lower than that reported previously for rural Kenyan women (17?2 g/d) (53) . However, energy from saturated fat and Na were positively associated with membership duration.…”
Section: Nutrition Transitioncontrasting
confidence: 66%
“…The higher proportion of overweight member women reflects this transition and is an area of concern. Energy from saturated fat remained below the recommended level (10 %) and median intake was lower than that reported previously for rural Kenyan women (17?2 g/d) (53) . However, energy from saturated fat and Na were positively associated with membership duration.…”
Section: Nutrition Transitioncontrasting
confidence: 66%
“…These associations were independent of behavioural factors including physical activity, smoking and alcohol consumption, and results of the structural equation model confirmed that the association was not mediated by lifestyle. The sex-specific associations highlight the complexity of the association between SES and BMI with studies showing both positive and negative associations in both sexes [10,32,33]. Puoane et al, using data from the South African Demographic and Health Survey, have shown that the association between education and BMI may not be linear in South African women as they showed that women with no formal education and women with tertiary education had a lower BMI than women with some schooling [34].…”
Section: Discussionmentioning
confidence: 99%
“…In this chapter, the models for eastern and western Turkey are estimated by regressing the RIFR of BMI on the vector of covariates for each quartile 3 : where (12) where is the quantile of BMI, is the unconditional quantile of BMI for eastern and western Turkey, is the unconditional density of BMI at τth quantile, is an indicator function for whether outcome variable is smaller or equal to the τth quantile, is the vector of covariates and is the coefficient of the RIF regression that captures the marginal effect of a change in distribution of characteristic on the unconditional quantile of BMI. Therefore the difference between eastern and western Turkey (11) at the τth quantile of BMI can be decomposed into composition and structural effects as follows: (13) (14) (15) then structural and composition effect can be written in terms of the sum of contribution of each covariate as: (16) (17) where indicates the omitted group effect, and indicate the element of and at quartile respectively.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, economists have focused on socio-economic status as a determinant of obesity, in both developed and developing countries, and have generally obtained quite different results [3], [5], [6], [8]- [12]. Broadly speaking, obesity is more prevalent among lower socio-economic groups (than among their better-off counterparts) in developed countries, while in developing countries it is more prevalent among higher socio-economic groups [9], [13]- [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation